The analysis of the response to the occupational stress among nurses - Śniegocka, Magdalena; Śniegocki, Maciej (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction and aims. Factors influencing human health are, among others, conditions connected with work performed by them professionally. As far as nurses are concerned, stress factors arise due to contacts with patients and members of their families, conflicts in relations with their colleagues, as well as their superiors. The aim of this article was the assessment of the stress levels on the basis of a selected group of nurses, together with the nature of work-related strategies selected most often by surgery nurses (surgical or perioperative nurses). Material and methods. The study was conducted by diagnostic poll method using a questionnaire survey distributed among 44 nurses working in surgical departments in Warsaw. For the purpose of this analysis, COPE questionnaire was applied, i.e. a multilevel inventory measuring ways of coping with stress by Carver et al., adapted into Polish by Juczyński and Ogińska-Bulik. The study was complimented with socio-demographic questions concerning age, education and the character of work performed. Furthermore, questions regarding stress factors along with manners of coping with it were asked. Results. Only women took part in the study. The average age of the research group was 40.7 years, while the average time of practicing their profession was 19.1 years. The most frequent sources of stress indicated by the respondents were work overload, in particular administrative duties, low payment and staff shortages. Subjectively perceptible stress levels among the respondents reached high levels and amounted to 7.1 (on a 1–10 scale). The data analysis showed that nurses under the age of 40 while practicing their profession tend to apply techniques focusing on planning and active coping with problems, as well as employ avoidance behaviours, consisting in acceptance of stressful situations. Conclusions. Stress levels perceived by the surgery nurses should be considered high. The application of the planning strategy and active coping with stress factor depends on education. Age influences how frequently both the strategy of avoidance of competitive behaviour, as well as the sense of humour as a means of relieving tense situations are applied. The time of work in their profession contributes to application of techniques focusing on a problem, together with avoidance behaviours. The levels of perceived stress determines behaviours aiming at active solving of a problem, as well as revaluation and development. Nursing Topics 2014; 22 (4): 503–510